Co-production on the Edge of Project and Process Management - The Sijtwende development project - Jurian Edelenbos; Geert Teisman (European Regional Science Association (ERSA), 2005)
The goal of this paper is to describe and analyze co-production in public private partnerships in spatial planning. We will describe one specific case study, the location development project Sijtwende on the edge of two municipalities (The Hague and Voorburg), on the edge of public and private investments and on the edge of urban development and extension of the mobility system. We will elaborate the bottlenecks in the cooperation between several actors involved. Furthermore we will look for important breakthroughs in the process of collaborative development of the area. How was it possible that after a public lock in situation that took more than twenty years a private party was able to force a breakthrough? Finally we will deal with the question what this case learns us for the management of these complex processes of co-production. We will combine theoretical thoughts and empirical insights from our in-depth case study in order to find balances in using project management and process management strategies for managing complex spatial planning processes.
Keywords: 330